1999
DOI: 10.1177/030802269906200204
|View full text |Cite
|
Sign up to set email alerts
|

How do Occupational Therapists define their Role in a Community Mental Health Setting?

Abstract: The aim of this study was to examine how occupational therapists define their role In a community mental health setting, within a framework of current concern about a lack of knowledge and recognition of the profession among both other health professionals and the general public, Including clients of the service. Nineteen practising occupational therapists were interviewed by telephone and invited to give their definitions of occupational therapy.The main finding was that there was a lack of a uniform definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…With the shift to community-based care, there is an emphasis on teamwork and an interdisciplinary perspective. Concerns have been raised in the occupational therapy literature about the blurring of roles and lack of understanding about the functions of occupational therapy in community mental health (Kaur et al, 1996;Taylor and Rubin, 1999). Leonard and Corr (1998) found that lack of professional identity and low status of the profession were stressors for newly qualified occupational therapists.…”
Section: Professional Rolementioning
confidence: 99%
“…With the shift to community-based care, there is an emphasis on teamwork and an interdisciplinary perspective. Concerns have been raised in the occupational therapy literature about the blurring of roles and lack of understanding about the functions of occupational therapy in community mental health (Kaur et al, 1996;Taylor and Rubin, 1999). Leonard and Corr (1998) found that lack of professional identity and low status of the profession were stressors for newly qualified occupational therapists.…”
Section: Professional Rolementioning
confidence: 99%
“…However, they felt invisible, misunderstood, stereotyped by traditional images, and undervalued by those in related professions. In many studies, the occupational therapy professionals’ self‐esteem and roles have been described as complex and multifaceted (Booth & Hewison, 2002; Finlay; Lycett, 1991; Sachs & Jarus; Sachs & Labovitz, 1994; Taylor & Rubin, 1999; Vogel, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The word ‘independence’ was most commonly used. Likewise, Taylor and Rubin's (1999) main findings showed that occupational therapists working in community mental health care lacked a uniform definition of occupational therapy, but ‘activities of daily living’, ‘balancing roles’ and ‘independence’ were the most regularly cited phrases. Matching these findings, Björklund (1998) found unifying factors in the local ideology of occupational therapists from different health‐care settings, in which the characteristic of the occupational therapist's role as ‘an everyday coordinator’ was central (Björklund).…”
Section: Introductionmentioning
confidence: 99%
“…Proceeding debate within the professional literature focussed on the occupational therapy pre-registration curriculum; key areas of contention focussed on the mental health component and the importance of professional core skills 9,17,18 . Professional insecurity and role uncertainty experienced by occupational therapists working in mental health have been well documented over the past decade 20,21,22,23,24,25,26 . Reasons for this uncertainty are varied, yet tend to be linked to the fact that the scope of our practice is both broad and individualistic.…”
Section: Background Literaturementioning
confidence: 99%